Monitoring intracellular metabolites in neuroblastoma with 1H NMR spectroscopy: effects of growth factor withdrawal and modulation of lipid metabolism. Issue 2 (2004) - Lindskog Lindskog, Magnus Magnus; Jarvet Jarvet, Jüri Jüri; Graslund Graslund, Astrid Astrid; Kogner Kogner, Per Per
Abstract : 1 H NMR spectroscopy has previously been employed to detect and monitor changes in the lipid metabolism of neuroblastoma cells upon cytotoxic treatment. Here, we addressed the question whether altered growth conditions, by presence or absence of serum, would impact on the metabolites detectable with 1 H NMR spectroscopy. Chronic serum deprivation of SH‒SY5Y human neuroblastoma cells resulted in a decrease in the intracellular content of several metabolites, in particular total choline. This metabolic effect was paralleled by significant growth inhibition. In addition, we investigated the potential functional origin of intracellular 1 H NMR visible lipids in SH‒SY5Y cells. A drop in lipid methylene protons could be observed shortly after serum‒withdrawal. Contrary, removal of lipoproteins from the serum led to a pronounced increase in intracellular lipids, as did inhibition of de novo sterol synthesis by lovastatin. In conclusion, we demonstrate that intracellular total choline in neuroblastoma cells in vitro is highly dependent on the availability of growth factors. Furthermore, we show that 1 H NMR visible lipids decrease upon serum‒withdrawal but are accumulated when cholesterol supply is abrogated. The biological and potential clinical implications of these findings are discussed.